The Legal Reform of Venture Capital Financing Institutions As a Financing Alternative for Micro Small and Medium Enterprises - Tri Setiady (Universitas Lampung, 2021)
So far, the role of venture capital has not been optimal, or it can be said that while it is not working. In practice, in Indonesia, venture capital companies carry out their business like banking. That until now, in general, venture capital companies practice more as credit providers as the usual practice of providing bank loans. All requirements and conditions requested for a business partner company (actually: a debtor) are like a bank in giving credit. Therefore a legal reform of venture capital financing institutions is needed to optimize financing for micro, small, and medium enterprises to realize national development.